Shaikh ‘Alā` al-Dīn Alī al-Bahlawān and His Annotation on Tafser Al-Kashshāf of Al-Zamakhsharī | الشيخ علاء الدين علي البهلوان وحاشيته علي تفسير الكشاف للزمخشري - Khubby Mulyono (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2015)
This study about Shaikh ‘Alā` al-Dīn Alī al-Bahlawān annotation on tafser al-Kashshaf, begins with revealing the figure of al-Bahlawān, then dissect his annotation method on al-Kashshaf. This research revealed that al-Bahlawan pinned some reference to the muslim scholars, analyzing vocabulary by basing on dictionaries, and criticism of al- Zamakhsharī Mu'tazila understand.